Technical note: LIMS observations of lower stratospheric ozone in the southern polar springtime of 1978 - Remsberg, Ellis; Harvey, V. Lynn; Krueger, Arlin; Gordley, Larry; Gille, John C.; Russell III, James M. (Atmospheric Chemistry and Physics, 2020)
The Nimbus 7 Limb Infrared Monitor of the Stratosphere (LIMS) instrument operated from 25 October 1978 through 28 May 1979. This note focuses on its Version 6 (V6) data and indications of ozone loss in the lower stratosphere of the Southern Hemisphere subpolar region during the last week of October 1978. We provide profiles and maps that show V6 ozone values of only 2 to 3 ppmv at 46 hPa within the edge of the polar vortex near 60∘ S from late October through mid-November 1978. There are also low values of V6 nitric acid (∼3 to 6 ppbv) and nitrogen dioxide (< 1 ppbv) at the same locations, indicating that conditions were suitable for a chemical loss of Antarctic ozone some weeks earlier. These “first light” LIMS observations provide the earliest space-based view of conditions within the lower stratospheric ozone layer of the southern polar region in springtime.